The Interaction between Human and Organizational Capital in Strategic Human Resource Management - Junita, Audia (International Research Journal of Business Studies, 2016)
Studies in strategic human resource management emphasize the contribution of human and human resource management to organizational performance achievement. Human and organizational capitals are strategic capability and mechanism to create value in an organization.This paper seeks to identify an interactive relationship between human and organizational capital in strategic human resource management theoretically, which so far, have not got adequate attention, particularly in a systemic relationship. Library research has been conducted either through books, articles and previous studies related to the issues have been analyzed. It is found that there is an interactive relationship between human resource system as an element of organizational capital and role behavior as an element of human capital, in strategic human resource management, systemically. Organizational capital refers to a human resource system can enhance the strategic value of human capital through their role behavior. Role behavior, then, not only is positioned as an output, but also an input for the desired human resource system, as organizational capital. The result of the theoretical study needs to be followed up by empirical research, to validate the proposed interactive relationship between human and organizational capital.